Effect of Biological Fouling on the Dynamic Responses of Integrated Foundation Structure of Floating Wind Turbine and Net Cage - Yu Hu; Hao Liu; Yingyao Cheng; Jichao Lei; Junxin Liu (Journal of Marine Science and Engineering, 2025)
This paper proposes a novel integrated foundation structure of floating wind turbine and net cage by combining large capacity semi-submersible wind turbines with aquaculture cages. The research mainly focuses on the effect of biological fouling on net cage structures and safety performance of mooring systems. The study firstly validates the simplified model of net cage through comparing with results of existing scaled experimental models. Then, a hydrodynamic analysis is conducted on the net cage model to obtain the RAOs of motion response of the structure under frequency-domain analysis, and damping correction is also carried out on the structure. Finally, time-domain analyses under irregular wave conditions are conducted to evaluate the effects of biofouling fouling on motion responses of net cage foundation and tensions of mooring lines.